Technopreneurship and Digital Innovation as Determinants of MSME Competitive Advantage: A Strategic Management Perspective in the Digital Economy Era - Burhanuddin Burhanuddin; Eddy Soeryanto Soegoto; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar; Rahma Wahdiniwaty (Journal Research of Social Science, Economics, and Management, 2026)
Digital transformation is understood as a systematic process that influences the entire management cycle—from strategy formulation and implementation to organizational performance evaluation. This study aims to analyze the effect of digital innovation, technopreneurial managerial competence, and technology orientation on the competitive advantage of Small and Medium Enterprises (SMEs). A quantitative approach was employed using a survey method involving 150 SME respondents who had adopted digital technologies, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital innovation, technopreneurial managerial competence, and technology orientation have a positive and significant impact on SMEs’ competitive advantage, explaining 71.7% of the variance. These findings highlight the importance of integrating technopreneurship and digital innovation as an effective managerial strategy to enhance the competitiveness and sustainability of SMEs. The study provides practical implications for SME owners to prioritize managerial competence development, technology adoption, and innovation culture while offering guidance for future research to consider external factors influencing competitive advantage models.